1998
DOI: 10.1136/emj.15.5.312
|View full text |Cite
|
Sign up to set email alerts
|

Can x rays be accurately interpreted using a low cost telemedicine system?

Abstract: Objective-To assess whether the quality of x ray films transmitted via a low cost (low resolution) telemedicine link was satisfactory for clinical diagnosis. Methods-A retrospective study of a set of consecutive accident and emergency (A&E) radiographs. An A&E registrar viewed these directly on a standard x ray viewing box and via a telemedicine link. Results-There were 81 abnormalities out of 234 x ray films. Three abnormalities were missed both on the x ray viewing box and telemedicine link, one of which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
2
7
0
2
Order By: Relevance
“…Diagnostic accuracy and reliability of real‐time telemedicine compared with face‐to‐face consultations is between 59% and 80% in the literature (8). These findings are similar for store‐and‐forward methods giving diagnostic agreement between 59% and 93% in various studies (9–14).…”
Section: Accuracy and Reliabilitysupporting
confidence: 79%
“…Diagnostic accuracy and reliability of real‐time telemedicine compared with face‐to‐face consultations is between 59% and 80% in the literature (8). These findings are similar for store‐and‐forward methods giving diagnostic agreement between 59% and 93% in various studies (9–14).…”
Section: Accuracy and Reliabilitysupporting
confidence: 79%
“…52 An A&E teleradiology system was recently reported by O'Reilly and colleagues from Belfast. 63 This suggested that plain radiographs could be adequately interpreted, for the purposes of minor injuries management, using a low cost and low resolution telemedicine link. This is supported by other papers that have shown that a reduction in the cost and technical specifications of a teleradiology system may still yield adequate images.…”
Section: What Is the Accuracy Of Teleradiology In Relation To Currentmentioning
confidence: 99%
“…15 Most studies judge the technical image quality and do not consider the simultaneous evaluation of the clinical information provided. 16 In the present study, both the quality of images transmitted via teleconferencing and the clinical relevance of real-time interactive discussion is analyzed to determine the benefits, if any, to the diagnostic accuracy in the field of surgery.…”
Section: Commentmentioning
confidence: 99%